Conservation and Diversity in Gibberellin-Mediated Transcriptional Responses Among Host Plants Forming Distinct Arbuscular Mycorrhizal Morphotypes - Tominaga, Takaya; Miura, Chihiro; Sumigawa, Yuuka; Hirose, Yukine; Yamaguchi, Katsushi; Shigenobu, Shuji; Mine, Akira; Kaminaka, Hironori (Frontiers in Plant Science, 2021)
Morphotypes of arbuscular mycorrhizal (AM) symbiosis, Arum, Paris, and Intermediate types, are mainly determined by host plant lineages. It was reported that the phytohormone gibberellin (GA) inhibits the establishment of Arum-type AM symbiosis in legume plants. In contrast, we previously reported that GA promotes the establishment of Paris-type AM symbiosis in Eustoma grandiflorum, while suppressing Arum-type AM symbiosis in a legume model plant, Lotus japonicus. This raises a hitherto unexplored possibility that GA-mediated transcriptional reprograming during AM symbiosis is different among plant lineages forming different AM morphotypes. Here, our comparative transcriptomics revealed that several symbiosis-related genes were commonly upregulated upon AM fungal colonization in L. japonicus (Arum-type), Daucus carota (Intermediate-type), and E. grandiflorum (Paris-type). Despite of the similarities, the fungal colonization levels and the expression of symbiosis-related genes were suppressed in L. japonicus and D. carota but were promoted in E. grandiflorum in the presence of GA. Moreover, exogenous GA inhibited the expression of genes involved in biosynthetic process of the pre-symbiotic signal component, strigolactone, which resulted in the reduction of its endogenous accumulation in L. japonicus and E. grandiflorum. Additionally, differential regulation of genes involved in sugar metabolism suggested that disaccharides metabolized in AM roots would be different between L. japonicus and D. carota/E. grandiflorum. This study uncovered the conserved transcriptional responses during mycorrhization and diverse responses to GA among phylogenetically distant AM host plants with distinct morphotypes.